Relationship between Parathyroid Hormone Level and Early Remodeling Heart Failure after Acute Myocardial Infarction - Zohreh Firouzi; Saeideh Mahdizadeh Sajjadieh; Maryam Mousavi; Zahra Erfanian; Maryam Zarif (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background: Previous studies have indicated that parathyroid hormone (PTH) has been linked to post-myocardial infarction (MI) development. The aim of this cross-sectional study was to evaluate the relationship between PTH level and heart failure due to post infarction remodeling during the first 72 hours of hospitalization. Methods: Seventy patients with a diagnosis of acute MI (age ≥18 years, 22 females and 48 males) were enrolled. Patients were admitted to the Imam Raza Educational, Research and Treatment Center, Mashhad University of Medical Sciences, Iran between July 2014 to September 2015. We measured PTH and vitamin D level. Blood samples were taken after 24 hours and 72 hours. Results: During the first 72 hours, the PTH level significantly increased in patients with Post-MI heart failure. 68% of the subjects had an inappropriate vitamin D level at the time of admission. Mean levels of vitamin D and PTH increased compared with the baselines (95% CI, 0.15 to 10.03, P: 0.044), (95% CI, 6.5 to 24.8, P:0.001) respectively. Conclusion: Acute elevations of serum PTH levels increased early remodeling heart failure after MI. Serum vitamin D status was independent of high serum PTH level. Based on the current evidence, PTH excess may be a risk factor for heart failure, so early treatment and omitting risk factors are the most effective strategies for the patients with acute myocardial infarction.